Analisis Determinan Investasi Portofolio Asing (Studi Komparatif: Indonesia-China) - Lusiana Prastiwi; Idris Idris (Universitas Negeri Padang, 2020)
This research explains about Analysis Determinants Of Foreign Portfolio Investment (Comparative Study : Indonesia - China). This research uses a time series data from year 1986 - 2018, with method Error Correction Model (ECM). Data sources from World Bank and Global Rates. Research result explain that (1) Long-term and short economic growth in Indonesia and China has a significant positive to FPI (2) International interest rate long-term and short-term in Indonesia and China has a insignificant positive effect on FPI (3) Dummy economic crisis long-term in Indonesia increases foreign portofolio investment, but in China lowers foreign portofolio investment . Meanwhile short-term in Indonesia and China increases investment.